2020
DOI: 10.1007/s00334-020-00770-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative landscape reconstruction and erosion history during the past 1,100 years in the Skogaryd Research Catchment, southern Sweden

Abstract: A sediment sequence from a small forest lake in southwestern Sweden was investigated to explore the effects of forestry and land-use on catchment erosion and delivery of organic and minerogenic matter to the lake. Catchment-scale vegetation changes during the last 1,100 years were reconstructed quantitatively at 50-year resolution using pollen analysis and the Landscape reconstruction algorithm (LRA). Variations in terrestrial organic matter input to lake sediments were assessed by total organic carbon (TOC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…However, as indicated by Λ 8 , the contribution of terrestrial OM was still higher than it was before the 18th century when the catchment experienced minor human impacts. A similar case has also been observed in the sediment of a lake located in southwestern Sweden (Yang et al., 2020, 2021). Many studies have reported an initial loss in soil OM after reforestation partly resulting from pre‐planting disturbances, and the soil carbon stock level is lower in a managed conifer forest than in a comparable natural forest (Bastida et al., 2018 and references therein).…”
Section: Discussionsupporting
confidence: 77%
“…However, as indicated by Λ 8 , the contribution of terrestrial OM was still higher than it was before the 18th century when the catchment experienced minor human impacts. A similar case has also been observed in the sediment of a lake located in southwestern Sweden (Yang et al., 2020, 2021). Many studies have reported an initial loss in soil OM after reforestation partly resulting from pre‐planting disturbances, and the soil carbon stock level is lower in a managed conifer forest than in a comparable natural forest (Bastida et al., 2018 and references therein).…”
Section: Discussionsupporting
confidence: 77%
“…Non-temperature-related changes in zooplankton abundance as, for example, driven by terrestrial nutrient run-off variability might also be variously modelled using evidence for inter-related changes in settlement, land-cover, storminess and streamflow (e.g. Bunzel et al, 2021; Johansson et al, 2020; Lamb and Frydendahl, 1991; Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%